Influence of Grain Particle Size and Insoluble Fiber Content on Salmonella Colonization and Shedding of Turkeys Fed Corn-Soybean Meal Diets - Santos, F.B.O.; Santos Jr., A.A.; Ferket, P.R.; Sheldon, B.W. (International Journal of Poultry Science, 2006)
This study aimed to determine the impact of feeding partially ground corn or insoluble fiber on intestinal development, Salmonella cecal colonization and fecal shedding of turkeys from 0-28d. Turkeys reared in cage-batteries were assigned to 1 of 3 diets: ground corn-SBM (GC, TRT 1), coarse ground corn-SBM (CC, TRT 2), and 4% wood shavings + ground corn-SBM (SC, TRT 3). A 3-strain cocktail of nalidixic acid-resistant Salmonella enterica serotypes Hadar, Javaina, and Typhimurium was orally-gavaged into each poult at placement. Cecal and fecal Salmonella populations, growth performance and intestinal weights and lengths were measured. The diets had no impact on Salmonella cecal or fecal populations. At 28d, Salmonella cecal populations decreased approximately 3-logs (range: 2.4-3.3 log reduction) across all treatments in comparison to 7d (P< 0.0001). At 28d body weight, body gain and feed conversion ratio were not impacted by the diets. However, at 14d poults consuming the SC diet had lower feed consumption than those fed the GC and CC diets (231 vs. 243 and 252 g, P=0.001, respectively). The CC diet resulted in heavier relative gizzard weights at 28d in comparison to the GC and SC diets (30 vs. 28 and 22 g/kg, respectively, P< 0.0001). Conversely, the SC treatment reduced the mass of the small intestine relative to body weight, especially the jejunum. Dietary inclusion of coarsely ground corn and wood shavings had no adverse effect on growth performance yet improved gizzard and intestinal development, which could have positive effects on intestinal health.